2017
DOI: 10.1186/s12936-017-2067-6
|View full text |Cite
|
Sign up to set email alerts
|

The underlying reasons for very high levels of bed net use, and higher malaria infection prevalence among bed net users than non-users in the Tanzanian city of Dar es Salaam: a qualitative study

Abstract: BackgroundBed nets reduce malaria-related illness and deaths, by forming a protective barrier around people sleeping under them. When impregnated with long-lasting insecticide formulations they also repel or kill mosquitoes attempting to feed upon sleeping humans, and can even suppress entire populations of malaria vectors that feed predominantly upon humans. Nevertheless, an epidemiological study in 2012 demonstrated higher malaria prevalence among bed net users than non-users in urban Dar es Salaam, Tanzania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(84 citation statements)
references
References 30 publications
16
67
1
Order By: Relevance
“…This increment could be attributed to Uganda national malaria control program interventions of universal coverage of bed nets in the region as recommended by World Health Organization policy on ITN and accompany by free nets to pregnant women and infants in the country [5,30,31]. Our ndings are consistent with reports carried out in Tanzania with 80% bed net coverage [32,33] and other parts of the world [3] but higher than those reported in Kenya and other parts of Tanzania [33][34][35]. Our results also show that the incidence of malaria in children and adult were strongly related to lack of bed net or lack of use thereof and directly associated with the number of individuals spending a night together in a house which is similar to that observed in other studies in Africa [36,37].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This increment could be attributed to Uganda national malaria control program interventions of universal coverage of bed nets in the region as recommended by World Health Organization policy on ITN and accompany by free nets to pregnant women and infants in the country [5,30,31]. Our ndings are consistent with reports carried out in Tanzania with 80% bed net coverage [32,33] and other parts of the world [3] but higher than those reported in Kenya and other parts of Tanzania [33][34][35]. Our results also show that the incidence of malaria in children and adult were strongly related to lack of bed net or lack of use thereof and directly associated with the number of individuals spending a night together in a house which is similar to that observed in other studies in Africa [36,37].…”
Section: Discussionsupporting
confidence: 89%
“…What was very surprising is that despite achieving high coverage of IRS and ITNs in the study area, there was still high malaria incidence reported among the local communities which is similar to what has been observed in other African countries [34,35]. Of the 605 total number of individuals, 255 had malarial in the three months prior to this study, 171 of which were children (67%, a ratio of 3:2).…”
Section: Discussionsupporting
confidence: 60%
“…Our finding of a null association in the univariate analysis between pfPR and ownership of mosquito bed nets or using them the night before interview echoes our findings in Uganda [23] and Kenya [27] obtained using similar methodology as well as other reports in Tanzania [28,29] and elsewhere [23,27,30]. These results highlight an emerging concern that mosquito bed nets are losing their effectiveness as a key tool for malaria control, while the successful implementation of bed nets programs provides a false sense of security.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, current vector control tools face several challenges, which include sub-optimal user compliance [5] the rapid spread of insecticide resistance [6,7] mosquito behavioural changes after implementation of interventions [8], and implementation costs. All these factors combined greatly undermine the effectiveness of current intervention packages [2].…”
Section: Introductionmentioning
confidence: 99%